Providing A Half Sitting Position to Pulmonary Tuberculosis Patients In The Seruni Treatment Room At The Central General Hospital - Dunggio, Abdul Rivai Saleh; Mustari, Sahdan; Badaruddin, Badaruddin; Nuryani, Siti; Mustamin, Rini (International Journal of Health Sciences, 2024)
The lungs are one of the vital organs in the human body. To be precise, it is a respiratory (breathing) organ which is related to the respiratory and circulatory systems (blood circulation). Pulmonary tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis. Meanwhile, Relapsed Pulmonary Tuberculosis is a patient with Pulmonary Tuberculosis who is declared cured or has had complete treatment and then comes back for treatment with a positive test result for a cough with phlegm from Acid-Fast Basil. The aim of this study was to determine the risk factors for pulmonary tuberculosis at the Central General Hospital of South Sulawesi. This research uses a cross sectional approach. The population in this study includes the case population, namely pulmonary tuberculosis sufferers who experienced a recurrence and the control population, namely pulmonary tuberculosis sufferers who have been declared cured. The sample in this study was all data on patients with Relapsed Pulmonary Tuberculosis who received treatment at the Central General Hospital of South Sulawesi Province. Data analysis was carried out univariate and bivariate using the chi square test. The results of the study can be concluded that there is no relationship between age and the incidence of relapse of pulmonary tuberculosis. The problem and diagnosis determined is to fulfill the need to breathe normally and the inability to fulfill the need to eat and drink enough. Meanwhile, the nursing intervention that was prepared was directed at helping to control the patient's low-fat and low-salt diet regarding sitting therapy in the Semi-Fowler position. This theory can be applied and applied well in treatment focused on pulmonary tuberculosis cases. For pulmonary tuberculosis patients who experience shortness of breath, improve the quality of their breathing by performing the semi-Fowler position as a non-pharmacological therapy.